Elevated temperature promotes growth and feed efficiency of farmed ballan wrasse juveniles (Labrus bergylta) - Cavrois-Rogacki, Thomas; Davie, Andrew; Monroig, Óscar; Migaud, Hervé (Aquaculture, 2019)
The expansion of ballan wrasse farming, used as a biological control against sea lice in Atlantic salmon, is constrained by the slow growth rate in the species and extended period required to reach deployment size. Rearing temperature and diets are the two main growth limiting factors in fish. In this study, farmed ballan wrasse juveniles were reared at 10, 13 and 16 °C over a period of 3 months and fed two different commercial diets commonly used in marine finfish, Otohime S2 and BioMar Symbio. At the end of the trial, fish growth was +125, +75 and + 25% compared to their initial weight in 16, 13 and 10 °C treatments, respectively. It was suggested that temperatures above 16 °C may promote growth even further. Furthermore, feed conversion ratio was significantly improved in fish reared at 16 °C. However, diets did not impact on any of the growth performance indicators although a significantly higher daily feed intake was observed in fish fed BioMar Symbio. Importantly, no significant effects of temperature and diets on mortality and condition factor were observed. No differences were found in the fish (whole-body) macronutrient composition between diets. Analysis of the protein, lipid and energy digestibility revealed lower apparent digestibility coefficients than normally observed in marine species, suggesting the diet formulation is not optimised for the species. Finally, fish reared at 10 °C showed increased hepatosomatic index, suggesting fat storage in the liver under cold temperatures. These results showed that the production cycle could be shortened by >4 months in fish reared at 16 °C. This could contribute to increase hatchery productivity and meet demand from the salmon production sector while reducing costs associated with the nursery phase although maintaining a constant high temperature would increase operational costs. The project and PhD studentship TCR were supported by a project co-funded by the Scottish Aquaculture Innovation Centre (SAIC) and industry partners.